2016
DOI: 10.1186/s12885-016-2443-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased neutrophil-to-lymphocyte ratio is associated with disease-specific mortality in patients with penile cancer

Abstract: BackgroundThe neutrophil-to-lymphocyte ratio (NLR), a simple marker of the systemic inflammatory response, has been demonstrated to correlate with patient outcomes for various solid malignancies. We investigated the utility of the pretreatment NLR as a prognosticator in patients who presented with penile cancer.MethodsA total of 41 patients who underwent complete blood count with differential and subsequent radical penectomy from 1988 to 2014 were analyzed. We assessed the correlation between the NLR and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Recently, an elevated ratio of peripheral neutrophils-to-lymphocytes (NLR) has been recognized as a poor prognostic indicator in penile cancer, Patients with a high NLR had signi cantly worse CSS [17,18] and OS [16];Patients with a low LMR had signi cantly worse RFS and CSS than those with a high LMR [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an elevated ratio of peripheral neutrophils-to-lymphocytes (NLR) has been recognized as a poor prognostic indicator in penile cancer, Patients with a high NLR had signi cantly worse CSS [17,18] and OS [16];Patients with a low LMR had signi cantly worse RFS and CSS than those with a high LMR [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an elevated ratio of peripheral neutrophils-to-lymphocytes (NLR) has been recognized as a poor prognostic indicator in penile cancer, Patients with a high NLR had significantly worse CSS [17,18] and OS [16];Patients with a low LMR had significantly worse RFS and CSS than those with a high LMR [18].…”
Section: Discussionmentioning
confidence: 99%
“…Kasuga et al (2016) found that a higher baseline neutrophil to lymphocyte ratio was associated with increased disease specific mortality in patients with penile cancer. Interestingly, increased lymphocyte baseline count was associated with improved prognosis in multiple malignancies, including melanoma patients treated with pembrolizumab, an anti-programmed death (PD)-1 immunotherapeutic agent (Weide et al, 2016).…”
Section: Discussionmentioning
confidence: 99%